The ALPINE−ALMA [C ii] Survey: on the nature of an extremely obscured serendipitous galaxy. Issue 1 (4th June 2020) - Romano, M; Cassata, P; Morselli, L; Lemaux, B C; Béthermin, M; Capak, P; Faisst, A; Le Fèvre, O; Schaerer, D; Silverman, J; Yan, L; Bardelli, S; et al.
ABSTRACT: We report the serendipitous discovery of a dust-obscured galaxy observed as part of the Atacama Large Millimeter Array (ALMA) Large Program to INvestigate [C ii ] at Early times (ALPINE). While this galaxy is detected both in line and continuum emissions in ALMA Band 7, it is completely dark in the observed optical/near-infrared bands and only shows a significant detection in the UltraVISTA K s band. We discuss the nature of the observed ALMA line, that is [C ii ] at z ∼ 4.6 or high- J CO transitions at z ∼ 2.2. In the first case, we find a [C ii ]/FIR luminosity ratio of log(L_[ C II]/L_ FIR) -2.5, consistent with the average value for local star-forming galaxies (SFGs). In the second case instead, the source would lie at larger CO luminosities than those expected for local SFGs and high- z submillimetre galaxies. At both redshifts, we derive the star formation rate (SFR) from the ALMA continuum and the physical parameters of the galaxy, such as the stellar mass ( M * ), by fitting its spectral energy distribution. Exploiting the results of this work, we believe that our source is a 'main-sequence', dusty SFG at z = 4.6 (i.e. [C ii ] emitter) with log(SFR/M_ yr^-1)1.4 and log( M * /M⊙ ) ∼ 9.9. As a support to this scenario our galaxy, if at this redshift, lies in a massive protocluster recently discovered at z ∼ 4.57, at only ∼1 proper Mpc from its centre. This work underlines the crucial role of the ALPINE survey in making a census of this class of objects, in order to unveil their contribution to the global SFR density at the end of the Reionization epoch.